Optimization of Agave tequilana Weber var. Azul Juice Spray Drying Process - Alejandra Chávez-Rodríguez; Irma G. López-Muraira; Juan F. Goméz-Leyva; Guadalupe Luna-Solano; Rosa I. Ortíz-Basurto; Isaac Andrade-González (Journal of Chemistry)
In this work, the response surface methodology was employed to optimize the microencapsulation of Agave tequilana Weber var. azul juice with whey protein isolated using a spray drying technique. A Box-Behnken design was used to establish optimum spray drying conditions for Agave tequilana juice. The process was optimized to obtain maximum powder yield with the best solubility time, hygroscopicity, bulk density, water activity, and reducing sugars. The independent parameters for the spray drying process were outlet temperature of 70–80°C, atomizer speed of 20000–30000 rpm, and airflow of 0.20–0.23 m3 s−1. The best spray drying condition was at outlet temperature of 80°C, atomizer speed of 20000 rpm, and air flow rate of 0.23 m3 s−1 to obtain maximum powder yield (14.65%bm), minimum solubility time (352.8 s), maximum bulk density (560 kg m−3), minimum hygroscopicity (1.9×10-7 kgwater s−1), and minimum aw (0.39). The Agave tequilana powder may be considered as an interesting source of dietary fiber used as food additive in food and nutraceutical industries.